Food Security and Cardiovascular Disease Risk Among Adults in the United States: Findings From the National Health and Nutrition Examination Survey, 2003–2008 - Ford, Earl S. (Centers for Disease Control and Prevention, 2013)
INTRODUCTION: Little is known about the relationship between food security status and predicted 10-year cardiovascular disease risk. The objective of this study was to examine the associations between food security status and cardiovascular disease risk factors and predicted 10-year risk in a national sample of US adults. METHODS: A cross-sectional analysis using data from 10,455 adults aged 20 years or older from the National Health and Nutrition Examination Survey 2003–2008 was conducted. Four levels of food security status were defined by using 10 questions. RESULTS: Among all participants, 83.9% had full food security, 6.7% had marginal food security, 5.8% had low food security, and 3.6% had very low food security. After adjustment, mean hemoglobin A1c was 0.15% greater and mean concentration of C-reactive protein was 0.8 mg/L greater among participants with very low food security than among those with full food security. The adjusted mean concentration of cotinine among participants with very low food security was almost double that of participants with full food security (112.8 vs 62.0 ng/mL, P < .001). No significant associations between food security status and systolic blood pressure or concentrations of total cholesterol, high-density lipoprotein cholesterol, or non-high-density lipoprotein cholesterol were observed. Participants aged 30 to 59 years with very low food security were more likely to have a predicted 10-year cardiovascular disease risk greater than 20% than fully food secure participants (adjusted prevalence ratio, 2.38; 95% CI, 1.31–4.31). CONCLUSION: Adults aged 30 to 59 years with very low food security showed evidence of increased predicted 10-year cardiovascular disease risk.